Pengembangan Bahan Ajar Fisika Dasar Berbasis Model Pembelajaran P3e Untuk Meningkatkan Keterampilan Berpikir Kritis Mahasiswa Program Studi Tadris Fisika - Bahtiar Bahtiar (Department of Physics Education, Universitas Mataram, 2018)
This research aims to cultivate our learning materials basic physics-based model of learning P3E to enhance students ' critical thinking skills. This research was carried out from June until October 2017 at UIN Mataram. The type of research used IE research development-oriented product development includes three phases, namely the preliminary studies, product development and testing products. Test your basic physics materials involving 36 students (two class) semester 2 academic year2016/2017 and extensive trials carried out on 49 students (two class) academic year 2017/2018 Prodi Tadris Physics FTK UIN Mataram. Products resulting from this research is a physics-based model of learning materials learning P3E consisting of four (4) syntax: organizing, investigation, evaluation, and presentation. Basic physics, materials physics material contain basic 1 sub staple in temperature and heat. The results of validation experts show all materials declared valid and reliability. Basic physics-based learning materials learning model used and effective practical P3E to enhance critical thinking skills. There for learning materials based models developed viable P3E learning used to enhance students ' critical thinking skills. ÃÂ